AtMYB32 regulates the ABA response by targeting ABI3, ABI4 and ABI5 and the drought response by targeting CBF4 in Arabidopsis - Li, Xinmei (Plant science : an international journal of experimental plant biology, 2021)
Copyright © 2021 Elsevier B.V. All rights reserved.